THE IMPLEMENTATION OF SHOWING OBJECT STRATEGY ON THE STUDENTS’ SPEAKING ABILITY AT THE SECOND GRADE OF MTS MUALLIMIN UNIVA MEDAN IN 2015/2016 ACADEMIC YEAR - Muhammad Dalimunthe (VISION, 2018)
This research was aimed to find out the effect of implementing showing object strategy on the students’ speaking ability. The subject of this research was eleventh grade of Mts Muallimin univa Medan in 2016 academic year. The object of this research was to improve students’ ability in speaking by using showing object strategy . This research of this study was conducted by using classroom action research. The technique of analyzing data of this research was applied by qualitative and quantitative data. The qualitative data were taken from observation sheet, diary notes, interview and documentation . the quantitative data were taken from the test. Data was taken from the result which was carried out in two cycle. And two cycles conducted in five meetings. The test was given to the students in form of pre-test, post-test in the first cycle, and post-test in the second cycle. The result of analyzing the data showed that there was an increasing on the students’ ability at speaking from each cycles. It was found the mean of pre-test score (59.31). where, there were 13 students got success score criteria (31.70%) and 28 students got unsuccessful (68.29%). After doing cycle I by using showing object strategy , there was an improving of the result of the students’ mean scores (68.36) where 20 students got successful criteria score (48.78%) and 21 students got unsuccessful criteria score (51.22%). then, for second cycle, there was improvement of students’ mean score (77.02). where, 35 students got success criteria score (85.36%) and 6 students got unsuccessful criteria score (14.63%). in other words, the students’ ability at speaking taught by using showing object strategy was improved. For the hypothesis testing used t-test formula, from the computation, it can be seen that coefficient of t-count (10.64) with fact level α = 0.05 was 2.05. In the coefficient of tcount (10.64) >ttable (2.05). Thus, alternative hyphothesis (Ha) could be received. Based on the finding, alternative hyphothesis (Ha) stating that showing object strategy could improve the students’ ability in speaking accepted  and could make class atmosphere more alive and active.Keyword:  students’ ability, showing object strategy, speaking